The Effect of KPI-Based Performance Appraisal on Generation Z Employee Performance at the Head Office of PT Basa Inti Persada - Muhamad Abid; Indra Januar Rukmana; Syawaludin Syawaludin (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background: The rise of Generation Z as a dominant segment of today’s workforce requires organizations to adjust performance appraisal systems to meet expectations for transparency, clarity, fairness, and participation. Prior studies show that traditional appraisal mechanisms often fail to match the behavioral characteristics and workplace needs of Generation Z, particularly in fast-paced industries such as retail. PT Basa Inti Persada, a modern Muslim fashion retail company, has implemented a Key Performance Indicator (KPI)-based performance appraisal system. However, its effectiveness in improving the performance of Generation Z employees has not yet been empirically validated.Purpose: This study aims to (1) describe the implementation of the KPI-based performance appraisal system at the head office of PT Basa Inti Persada, (2) assess the performance level of Generation Z employees, and (3) analyze the direct effect of KPI system effectiveness on their performance.Design/methodology/approach: The research used a quantitative approach with a structured survey. The study population included 68 Generation Z employees at the company’s head office, and 51 respondents were selected using purposive sampling based on age (born 1997–2012) and minimum work tenure of six months. Data were collected through validated questionnaires and analyzed using descriptive statistics, Pearson correlation, and simple linear regression to measure the effectiveness of the KPI system, employee performance, and the magnitude of influence between variables.Findings/Results: The KPI-based appraisal system was perceived as effective, with an average score of 67.20. Generation Z employee performance was relatively high, with an average score of 66.39. Correlation analysis revealed a strong positive relationship between KPI system effectiveness and employee performance (r = 0.796; p < 0.001). Regression analysis showed that 63.4% of the variance in performance is explained by the effectiveness of the KPI system (R² = 0.634). Hypothesis testing confirmed a significant influence, indicated by a t-value of 9.208 and p < 0.001.Conclusion: The findings indicate that the KPI-based performance appraisal system significantly improves Generation Z employee performance. Key contributing factors include indicator clarity, appraisal fairness, employee participation, and reward alignment. These elements support higher motivation, engagement, and sustained performance among Generation Z employees.Originality/value: This study contributes to the limited empirical research in Indonesia that connects KPI-based appraisal effectiveness with Generation Z characteristics in the modern Muslim fashion retail industry. The study provides practical insights and recommendations for organizations seeking to optimize performance appraisal systems that better align with the expectations of younger employees. Keywords:   employee performance, kpi-based performance appraisal system, performance appraisal, generation z, retail industry